33. Evaluating Digital Authoring Tools - Wilde, Russ (International Review of Research in Open and Distributed Learning, 2004)
As the quality of authoring software increases, online course developers become less reliant on proprietary learning management systems, and develop skills in the design of original, in-house materials and the delivery platforms for them. This report examines the capabilities of digital authoring software tools for the development of learning materials. Seven software tools are evaluated, representing the following categories: single purposes; activity creation; course development and presentation; general presentation; testing and assessment.